Lung Injury Is a Predictor of Cerebral Hypoxia and Mortality in Traumatic Brain Injury - Robba, Chiara; Asgari, Shadnaz; Gupta, Amit; Badenes, Rafael; Sekhon, Mypinder; Bequiri, Erta; Hutchinson, Peter J.; Pelosi, Paolo; Gupta, Arun (Frontiers in Neurology, 2020)
Background: A major contributor to unfavourable outcome after traumatic brain injury (TBI) is secondary brain injury. Low brain tissue oxygen tension (PbtO2) has shown to be an independent predictor of unfavorable outcome. Although PbtO2 provides clinicians with an understanding of the ischaemic and non-ischaemic derangements of brain physiology, its value does not take into consideration systemic oxygenation that can influence patients’ outcomes. This study analyses brain and systemic oxygenation and a number of related indices in TBI patients: PbtO2, partial arterial oxygenation pressure (PaO2), PbtO2/PaO2, ratio of PbtO2 to fraction of inspired oxygen (FiO2), and PaO2/FiO2. The primary aim of this study was to identify independent risk factors for cerebral hypoxia. Secondary goal was to determine whether any of these indices are predictors of mortality outcome in TBI patients. Materials and methods: A single-centre retrospective cohort study of 70 TBI patients ̶ admitted to the Neurocritical Care Unit (NCCU) at Cambridge University Hospital in 2014-2018, and undergoing advanced neuromonitoring including invasive PbtO2 ̶.was conducted. 303 simultaneous measurements of PbtO2, PaO2, PbtO2/PaO2, PbtO2/FiO2, PaO2/FiO2 were collected and mortality at discharge from NCCU was considered as outcome. Generalized estimating equations were used to analyse the longitudinal data. Results: Our results showed PbtO2 of 28 mmHg as threshold to define cerebral hypoxia. PaO2/FiO2 found to be a strong and independent risk factor for cerebral hypoxia when adjusting for confounding factor of intracranial pressure (ICP) with adjusted odds ratio of 1.78, 95% confidence interval of (1.10-2.87) and p-value=0.019. With respect to TBI outcome, compromised values of PbtO2, PbtO2/PaO2, PbtO2/FiO2and PaO2/FiO2 were all independent predictors of mortality while considered individually and adjusting for confounding factors of ICP, age, gender and cerebral perfusion pressure (CPP). However, when considering all the compromised values together, only PaO2/FiO2 became an independent predictor of mortality with adjusted odds ratio of 3.47 (1.20-10.04) and p-value=0.022. Conclusions: Brain and Lung interaction in TBI patients is a complex interrelationship. PaO2/FiO2 seems to be a major determinant of cerebral hypoxia and mortality. These results confirm the importance of employing ventilator strategies to prevent cerebral hypoxia and improve the outcome in TBI patients.